Impact of varying levels of sanitation on mortality of Tribolium castaneum eggs and adults during heat treatment of a pilot flour mill - Brijwani, Monika; Subramanyam, Bhadriraju; Flinn, Paul W. (My University, 2012)
The influence of sanitation on responses of life stages of the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), an economically important pest in flour mills, was investigated in a pilot flour mill subjected to two, 24-h heat treatments. One hundred eggs or 100 adults of T. castaneum were exposed inside each 20-cm diameter by 15-cm high PVC rings holding 0.1-, 0.2-, 1.0-, 3.0-, 6.0-, and 10.0-cm-deep wheat flour to simulate different sanitation levels that may exist in a flour mill. These rings were placed on the first and third floors of a pilot flour mill. On the first floor, temperatures inside rings with eggs reached 50 C in 7-11 h only in 0.1- and 0.2-cm-deep flour treatments. In all other treatments the maximum temperatures attained generally were below 50 C and inversely related to flour depth. Adults of T. castaneum on this floor were less susceptible than eggs. The egg mortality decreased linearly with an increase in flour depth, whereas that of adults decreased exponentially. All eggs and adults in rings on the third floor were killed irrespective of flour depth, because temperatures inside rings reached 50 C in 15-17 h and were held above 50 C for 6-8 h with the maximum temperatures ranging between 55.0 and 57.0 C. Although the protective effects of flour on survival of T. castaneum eggs and adults were evident only if temperatures did not reach 50 C, removal of flour accumulations is essential to improve heat treatment effectiveness.
Keywords: Heat treatment; Temperature; Sanitation; Red flour beetle; Efficacy assessment